2020
DOI: 10.1063/5.0002068
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature direct bonding of β-Ga2O3 and diamond substrates under atmospheric conditions

Abstract: Surface-functionalized β-Ga2O3 and diamond substrates were directly bonded by annealing at 250 °C in atmospheric air. Prior to bonding, the β-Ga2O3 and diamond surfaces were OH-terminated by oxygen plasma irradiation and H2SO4/H2O2 cleaning, respectively. After contacting the OH-terminated surfaces with each other, direct bonding was formed by a thermal dehydration reaction. The annealed specimen had a shear strength of 14 MPa because of the generation of chemical bonds between β-Ga2O3 and diamond surfaces. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…These applications include field-effect transistors and diodes for power electronics [14][15][16][17][18][19][20], microwave devices [21][22][23][24][25], deep-ultraviolet (DUV) light emitting diodes (LED) [26][27][28], DUV photodetectors [29,30], radiation detectors [31][32][33][34][35], microelectromechanical systems (MEMS) [36][37][38][39], and quantum sensors [40][41][42]. The utilization of diamond as a heat sink has also been attracting growing interesting in the application of high-power high-frequency communication, electrical power switch and others, in which the thermal dissipation is a problem [43][44][45][46][47]. Although great progress has been made in semiconductor diamond, diamond electronics is far from reality due to several bottlenecks such as the growth of large-area low-dislocation density SCD wafers, lack of shallow dopants, and poor interface between diamond and insulators in power electronics.…”
Section: Introductionmentioning
confidence: 99%
“…These applications include field-effect transistors and diodes for power electronics [14][15][16][17][18][19][20], microwave devices [21][22][23][24][25], deep-ultraviolet (DUV) light emitting diodes (LED) [26][27][28], DUV photodetectors [29,30], radiation detectors [31][32][33][34][35], microelectromechanical systems (MEMS) [36][37][38][39], and quantum sensors [40][41][42]. The utilization of diamond as a heat sink has also been attracting growing interesting in the application of high-power high-frequency communication, electrical power switch and others, in which the thermal dissipation is a problem [43][44][45][46][47]. Although great progress has been made in semiconductor diamond, diamond electronics is far from reality due to several bottlenecks such as the growth of large-area low-dislocation density SCD wafers, lack of shallow dopants, and poor interface between diamond and insulators in power electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Voids with diameters of approximately 0.1 mm were formed due to particles on the substrate surface. The large unbonded regions at the corners of diamond substrates resulted from the convex diamond surface (see the supplement of 34 ). If the environmental cleanliness and substrate flatness are improved, direct bonding will be formed at most of the contacted area.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group developed and reported a direct bonding method for semiconductor substrates (i.e., Si, Ga 2 O 3 ) on a diamond heat spreader [32][33][34][35][36] . We found that OH groups were formed on a diamond surface treated with oxidizing solutions, such as H 2 SO 4 /H 2 O 2 32 and NH 3 /H 2 O 2 mixtures.…”
mentioning
confidence: 99%
“…Voids with diameters of approximately 0.1 mm were formed due to particles on the substrate surface. The large unbonded regions at the corners of diamond substrates resulted from the convex diamond surface (see the supplement of 30 ). If the environmental cleanliness and substrate atness are improved, direct bonding will be formed at most of the contacted area.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group developed and reported a direct bonding method for semiconductor substrates (i.e., Si, Ga 2 O 3 ) on a diamond heat spreader [28][29][30][31][32][33] 34 . While studies on the bonding of InP and diamond are scarce, optoelectronics scientists have achieved the direct bonding of oxygen-plasma-activated InP lasers and Si waveguides [35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%